Sex and the patch: the influence of habitat fragmentation on terrestrial vertebrates' mating strategies. Issue 3 (4th May 2023) - Giuntini, Silvia; Pedruzzi, Luca
Abstract : The concept of mating systems refers to all the strategies through which animals interact in the context of breeding. Animal social interactions, and consequently their mating strategies, are strongly influenced by landscape configuration, including anthropogenic habitat fragmentation. Despite this holding the potential to impact both genetic viability and animal behaviour, an updated and comprehensive review on its effects on mating systems is lacking, as an exhaustive understanding of the underlying processes. Thus, we reviewed the literature concerning the influence of habitat fragmentation on mating systems of tetrapods and on processes associated with breeding. We underlined the unfortunate biases present in literature (e.g., most studies on birds and mammals, none on amphibians) and showed the changes possibly led by living in discontinuous habitats for each class of terrestrial vertebrates (i.e., mammals, birds, and reptiles). In fragmented patches of habitats, resource distribution gets altered; consequently, space occupancy may change and affect how animals interact, leading to variable potential for monogamous/polygamous mating systems compared to continuous populations. We discussed how dispersal and indirectly the population sex ratio can be altered in such populations, and further considered changes in social behaviour, specifically in interactions between kin individuals with increasing relatedness in smaller and isolated patches. More typical of bird populations are changes in mating-related phenomena such as pairing success, extra-pair paternity (EPP) rate, and nest parasitism, together with shifts from mating strategies (e.g., lekking behaviour). Although no univocal response to habitat parcelling was found, several complex and population-specific trends emerge in the literature. We suggest a multidisciplinary approach to implement research in this direction, especially to evaluate the adaptive nature of such responses. Ultimately, we underline the urgent need of taking into consideration behavioural responses in wildlife management interventions, particularly when dealing with species that may lack plasticity to adapt to landscape degradation.